2022
DOI: 10.3389/fphar.2022.958543
|View full text |Cite
|
Sign up to set email alerts
|

Investigating brain uptake of a non-targeting monoclonal antibody after intravenous and intracerebroventricular administration

Abstract: Monoclonal antibodies play an important role in the treatment of various diseases. However, the development of these drugs against neurological disorders where the drug target is located in the brain is challenging and requires a good understanding of the local drug concentration in the brain. In this original research, we investigated the systemic and local pharmacokinetics in the brain of healthy rats after either intravenous (IV) or intracerebroventricular (ICV) administration of EGFRvIII-T-Cell bispecific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…6 While the routes of administration in this report and our current study differ, it has been proposed that the transfer of antibodies from CSF to the interstitial fluid (ISF) of the brain, following ICV delivery, predominantly occurs after antibody transit back to serum. 42 Subsequently, they traversed the BBB to access the ISF.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 While the routes of administration in this report and our current study differ, it has been proposed that the transfer of antibodies from CSF to the interstitial fluid (ISF) of the brain, following ICV delivery, predominantly occurs after antibody transit back to serum. 42 Subsequently, they traversed the BBB to access the ISF.…”
Section: ■ Discussionmentioning
confidence: 99%
“…They observed a bell-shaped relationship between antibody size and brain exposure following IV delivery, with a 50 kDa Fab exhibiting the highest whole brain exposure among the analyzed antibodies . While the routes of administration in this report and our current study differ, it has been proposed that the transfer of antibodies from CSF to the interstitial fluid (ISF) of the brain, following ICV delivery, predominantly occurs after antibody transit back to serum . Subsequently, they traversed the BBB to access the ISF.…”
Section: Discussionmentioning
confidence: 99%
“…Early work showed that the insertion of a dialysis fiber into brain causes local brain injury leading to BBB disruption to both small molecules ( Morgan et al, 1996 ; Groothuis et al, 1998 ) and to large molecules such as albumin ( Westergren et al, 1995 ), and to the formation of a glial scar around the fiber ( Hascup et al, 2009 ). Recently, brain microdialysis has been applied to the brain delivery of monoclonal antibodies, where special fibers are used that have a MWCO of 1,000,000 Da ( Chang et al, 2018 ; Sopko et al, 2020 ; LePrieult et al, 2021 ; Van De Vyver et al, 2022 ). The assumption with this methodology is that the antibody distribution into the dialysate is a measure of antibody transport into the brain ISF.…”
Section: Development Of Therapeutic Antibodies For the Cns Without Bl...mentioning
confidence: 99%
“…In a recent study conducted by Van De Vyver et al, pharmacokinetics in the brains of healthy rats were modeled to analyze the effects of non-targeting mAbs administered via intravenous (IV) or intracerebroventricular (ICV) route [33]. Pathway analysis from their study suggested that antibody exposure in the interstitial fluid (ISF) of the brain is predominantly mediated by mAbs traversing the BBB rather than entering the ISF directly from the CSF, regardless of route of administration [33]. While some researchers have speculated that transcytosis of IgG antibodies may be facilitated by receptors on brain endothelial cells, such as the neonatal Fc receptor (FcRn), several studies have refuted this hypothesis [15,16,34].…”
Section: Non-specific Endocytosismentioning
confidence: 99%